Factors That Influence Work Quality - Alex Stepanus Sinaga, Richard; B, Mesra (PT. Multidisciplinary Press Indonesia, 2024)
This study examines the influence of compensation and work motivation on work quality at BPJS Employment in the Northern Sumatra Regional Office. Using quantitative methods and data collected from 80 employees, the research explores both the direct effects of compensation on work motivation and work quality, as well as the mediating role of motivation between compensation and work quality. The results indicate that compensation significantly affects work quality but has an insignificant direct impact on work motivation. However, motivation is a crucial mediating factor in enhancing the relationship between compensation and work quality.